REORIENTASI KURIKULUM PENDIDIKAN UIN AR-RANIRY: Kajian Terhadap Kurikulum Fakultas Dakwah dan Komunikasi - Fadhilah Fadhilah (Jurnal Ilmiah Didaktika, 2016)
Curriculum applied at the Islamic university and the State Islamic University (UIN), especially the Faculty of Da'wa and Communication, seems have some weaknesses that need to be the primary concern of the policy makers. This weakness can be seen from the number of subjects with general learning aims so each teacher can interpret the intent of the curriculum in various ways.In addition, the required credits are quite overload, so the main professionsthat are expected to arise from the majors or courses are not concrete and focused.Based on the description above, this paper tries to study, describe, and analyze thephilosophical framework of curriculum in Faculty of Da'wa descriptively, and suggest the reorientation of curriculum as well as the the actualization reconstruction of the curriculum of the Faculty of Da'wa and Communicationwhich has future oriented.